Direction for Physical Arrangement of Slums in Coastal Areas (Case Study: Liem Hie Djung Area, North Nunukan Village, Nunukan Regency) - Yoseph Yoseph (Publikasi Indonesia, 2024)
The process of urban development is always faced with various kinds of problems. One of the most important problems is the limited ability of cities to provide housing for residents who continue to grow and grow rapidly. The objectives of this study are: (1) To find out the extent of the level of slums in the Coastal Area around Liem Hie Djun, (2) To find out the correlation between the factors causing slums to the level of slums, and (3) To formulate directions for the arrangement of physical buildings of houses and the arrangement of basic infrastructure of the residential environment in the research area so that a residential environment with healthy and good environmental quality is realized. This research method uses the Spearman correlation method, and (3) The results of these two analyses are used as inputs in efforts to organize the slum environment, using the development analysis method. Based on the results of the analysis that has been carried out, it was found that the level of slums in RT 9 and RT 10 is heavy slums with weighting values of 374.8 and 328.5, respectively. Meanwhile, RT 11 is included in the category of medium slum level with a weighting value of 297. The results of the correlation analysis showed that the indicators of the level of health and comfort of buildings and environmental sanitation conditions had a perfect relationship that affected the level of slums. In RT 9, the level of health and comfort of buildings has a strong relationship affecting the level of slums.